The edition of Milan of the Latin translation of 'Sepolcri' by Ippolito Pindemonte (Prassi Ecdotiche della Modernità Letteraria, 2022)
At the Veneranda Biblioteca Ambrosiana is preserved the epistolary of Felice Bellotti (1786-1858), which bring the evidence of an editorial project implemented together with Camillo Ugoni for the publication of the princeps, posthumously, of a Latin translation in hexameters of the poem Sepolcri, written by Ippolito Pindemonte. Made by Gerolamo Federico Borgno in the 1910s, the translation has been published by Resnati in 1843. The research here presented has at its basis a reflection on the possibility of considering the printed translation truly authorial, in light of the fact that the original autograph did not arrive at the printer’s, but rather a transcription containing the variants introduced by Bellotti and Ugoni, who, however, published the text under the name of Federico Borgno. The two editors brought to the fore their own reading of the text, which differed according to the textual sensibility of each. A number of considerations are then made regarding the translation, and in particular the difficult balance between the necessary – but not always respected – fidelity to the original text and the stylistic and prosodic requirements, since it is a poetic version.
Keywords: Camillo Ugoni; Felice Bellotti; Federico Borgno; Biblioteca Ambrosiana; Milan; Sepolcri; Correspondence